Socially Insensitive Messages, Stereotypes and the Disadvantaged Others in the Czech Advertising - Renáta Sedláková (Communication Today, 2025)
Based on the theory of othering and the theory of stereotypes the author discusses a concept of the socially insensitive message. There are five key features defining such statements. Firstly, they latently communicate controversial meaning and are based on presumption that recipients will decode intended meaning on the basis of shared cultural knowledge. Secondly, they are based on the opposition of ‘We X They’. Thirdly, they speak about the Others and define them. These Others are members of socially disadvantaged groups and they are reduced to a few stereotypical features in these messages. Fourthly, the socially insensitive advertising utilizes humour and principle of jokes. Fifthly, these principles are related to commercial advertising with and their key ambition is to ensure a profit or benefit for producers. Most of such messages are examples of hate speech. Several cases are discussed in detail based on the semiotic case study analysis; advertisements on consumer goods, media, and political ideas are among them. The author regards these socially insensitive messages as ignored in general and in the long term not reflected critically in contemporary Czech society.